2022
DOI: 10.1149/1945-7111/ac87d7
|View full text |Cite
|
Sign up to set email alerts
|

The Electrochemical Detection of Dopamine Based on the Cobalt-Modified Nitrogen Doping Carbon Aerogels from Biomass

Abstract: The sensitive detection of dopamine (DA), especially the accurate monitoring of cell secreted DA, is necessary to the study of pathogenesis of central nervous system disease. Here, the cobalt-modified nitrogen doping carbon aerogels (Co-NCA) with three-dimensional pores were successfully synthesized through the hydrothermal and freeze-drying method of the biomass. As a natural substance, starch is the carbon source of Co-NCA, which is environmentally friendly. The electrochemically active area of an electrode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…30,31 It has become an important way to improve the performance of the detection sensor. [32][33][34][35] For example, Zhao et al found that carbon nanotube modified carbon-fiber electrodes had a better distinction for uric acid, DA and ascorbic acid, compared with pure carbon fiber electrodes; 36 Zhao et al used Ni(OH) 2 modified carbon fiber sensors combined with artificial intelligence to achieve the goal of efficient glucose detection. 37 At the same time, many studies have shown that ZnO is a non-toxic and biocompatible semiconductor material that is often used as a load for sensors due to its high potential and promising adsorption of biological macromolecules.…”
mentioning
confidence: 99%
“…30,31 It has become an important way to improve the performance of the detection sensor. [32][33][34][35] For example, Zhao et al found that carbon nanotube modified carbon-fiber electrodes had a better distinction for uric acid, DA and ascorbic acid, compared with pure carbon fiber electrodes; 36 Zhao et al used Ni(OH) 2 modified carbon fiber sensors combined with artificial intelligence to achieve the goal of efficient glucose detection. 37 At the same time, many studies have shown that ZnO is a non-toxic and biocompatible semiconductor material that is often used as a load for sensors due to its high potential and promising adsorption of biological macromolecules.…”
mentioning
confidence: 99%
“…[4][5][6] Consequently, it is significant to develop a convenient, sensitive and reliable method to detect dopamine in complex biological samples, especially the secreted from living cell. [7][8][9][10] In recent years, the dual-mode detection strategy attracted extensive attention and has been proved to be more effective than the single-mode method. [11][12][13][14][15] A variety of analytical methods, such as surface-enhanced Raman spectroscopy, fluorescence and high performance liquid chromatography have been applied to the analysis of DA.…”
mentioning
confidence: 99%